1974
DOI: 10.1051/apido:19740401
|View full text |Cite
|
Sign up to set email alerts
|

Mise en Évidence d'UN Cycle Saisonnier De La Teneur en Acides Céto-9 Et Hydroxy-9 Décène-2 Oïque Des Têtes De Reines Vierges d'ABEILLE

Abstract: (Apis mellifera ligustica S.) During a period extending from March 1971 to March 1972, a queenrearing was achieved each month by means of a simple grafting or larvae. All the young larvae were issued from the same colony of Italian bees (A. m. tigustica S.). The rearing took place in two to four rearing colonies used in sucession. Two days before the queen eclosion, the queen cells were taken out and placed into an incubator, together with some forty bees nearly born, and about ten hive-bees which were fed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
(4 reference statements)
0
4
0
1
Order By: Relevance
“…Pain et al (1974) found a seasonal pattern in the amount of 9-ODA and 9-HDA in the mandibular glands of virgin queens. For 9-ODA, a maximum appeared in June, possibly related to the spring swarming peak typical of honey bee colonies in temperate climates.…”
Section: Discussionmentioning
confidence: 80%
“…Pain et al (1974) found a seasonal pattern in the amount of 9-ODA and 9-HDA in the mandibular glands of virgin queens. For 9-ODA, a maximum appeared in June, possibly related to the spring swarming peak typical of honey bee colonies in temperate climates.…”
Section: Discussionmentioning
confidence: 80%
“…Il existe de nombreuses données concernant la corrélation entre l'âge et la production d'acide céto-9 9 décéne-2 oïque (acide céto-9) chez les reines (BU T L E R et PATON, 1962;PAIN et R OGE R, 1976, 1978PAIN et al, 1967PAIN et al, , 1972PAIN et al, , 1974 A l'aide d'une solution témoin d'acide céto-9 synthétique dilué dans l'acétone, que l'on injectait après chaque chromatogramme d'extrait de tête, on a pu savoir si de l'acide céto-9 était présent dans l'échantillon analysé et, si oui, dans quelle proportion (Fig. 1).…”
Section: Résuméunclassified
“…Thus, the extracts were prepared at the time of day when the production of 9-ODA is reported to be the highest, reaching 580 ~tg to 750 gg per queen in June at 11.00 h (Pain and Roger, 1978). The season corresponded to the beginning of a second peak of 9-ODA production (300-400 ~tg), measured in the same rearing and physiological conditions as ours (Pain et al, 1974).…”
Section: Discussionmentioning
confidence: 94%
“…470 gg) is higher than the amount usually mentioned in the literature (100-300 gg on average, reviewed by Velthuis, 1985). However, considerable variations occur depending on queen age, physiological state (unmated vs mated) (Pain et al, 1967;Crewe, 1982;Slessor et al, 1990;De Hazan et al, 1989), time of day (Pain and Roger, 1978) and season (Pain et al, 1974). Our extracts were obtained from 14-17-day-old unmated queens, killed at 10.00-11.00 h at the end of November.…”
Section: Discussionmentioning
confidence: 99%